PELATIHAN MENDELEY TERHADAP PENINGKATAN KEMAMPUAN SITASI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR - Joni Albar; Mastiah Mastiah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
: Citations are a mandatory part of writing academic books and other scientific articles. In fact, many STKIP Melawi students are confused or do not understand the art of scientific writing, citation procedures, and the use of the Mendeley application in their writings. As a result, there are only a few scientific papers or papers that do not fully follow the rules of citation and bibliography. The types of activities carried out in this PkM are training, in which resource persons provide material directly to participants, support in the practical application of the material provided, and interaction between speakers and participants. Consists of questions and answers and discussion. The target number is 50 students. The resource person for this training activity is the executor of the training activity itself, namely the PGSD STKIP Melawi lecturer who mastered the first material, citation techniques, and achieved an average score of 78. This shows that participants have a better understanding of the material than before participating in this training. , which is 48 . Participants' understanding of the second material, Techniques for Using Mendeley Applications was also higher than before attending this training, from an average score of 40 to an average score of 77. It can be downloaded to your computer or laptop, making it easy to automatically create a bibliography that spelled correctly. Mastering citation techniques in the Mendeley application will make it easier to create bibliography and improve your writing. The importance of this training is to add references according to the rules and get the main capital with good and correct writing